2022
DOI: 10.1101/2022.04.29.22274267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omics identify LRRC15 as a COVID-19 severity predictor and persistent pro-thrombotic signals in convalescence

Abstract: Patients with end-stage kidney disease (ESKD) are at high risk of severe COVID-19. Here, we performed longitudinal blood sampling of ESKD haemodialysis patients with COVID-19, collecting samples pre-infection, serially during infection, and after clinical recovery. Using plasma proteomics, and RNA-sequencing and flow cytometry of immune cells, we identified transcriptomic and proteomic signatures of COVID-19 severity, and found distinct temporal molecular profiles in patients with severe disease. Supervised le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Thus, while the emergence of a LRRC15 + pathological fibroblast population may ultimately drive the fibrotic changes observed in patients with COVID-19, these fibroblasts may initially play a protective role by contributing to viral clearance during the acute phase of infection through their expression of LRRC15 on the cell surface, subsequently paving the way for the transition toward tissue repair and remodeling. Importantly, while this article was under review, a multiomics study identified LRRC15 as a strong predictor of COVID-19 severity in human patients in a preprint [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while the emergence of a LRRC15 + pathological fibroblast population may ultimately drive the fibrotic changes observed in patients with COVID-19, these fibroblasts may initially play a protective role by contributing to viral clearance during the acute phase of infection through their expression of LRRC15 on the cell surface, subsequently paving the way for the transition toward tissue repair and remodeling. Importantly, while this article was under review, a multiomics study identified LRRC15 as a strong predictor of COVID-19 severity in human patients in a preprint [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CCL8, CXCL10, IL18, and IL6 (identified by all 3 platforms), and CCL7 (identified by Alamar and Olink) were found to be consistently upregulated in COVID-19 versus controls in a metaanalysis of five clinical studies (23). Many of the targets identified by the Alamar panel to be predictive of COVID-19 outcomes have been previously associated with outcome severity in COVID-19, e.g., GDF15 (24,25), S100A9 (26), IL17B (27), MDK (28), and IL12p70 (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…While our data highlights a new role for LRRC15 in promoting SARS-CoV-2 Spike binding, limiting infection, and regulating collagen expression, it is currently unclear how LRRC15 contributes to human COVID-19 disease. Notably, while this manuscript was under revision, a preprint authored by Gisby et al investigated serum from control and COVID-19 infected end stage kidney disease patients, and found that out of the entire serum proteome, depletion of circulating LRRC15 is the strongest predictor of COVID-19 clinical outcome 51 . Integrating these data, it is possible that fibroblast-expressed LRRC15, or potentially cell free LRRC15 deposits in the airways, could trap viral particles for subsequent clearance by the innate immune system, while at the same time enhancing cellular antiviral tone and suppressing fibrosis.…”
Section: Discussionmentioning
confidence: 99%